Effect of Sugar Types, Culture Age, Concentrations of 2,4?D and Sucrose on Somatic Embryogenesis of Cymbopogon schoenanthus subsp. proximus (Plant Tissue Culture and Biotechnology, 2015)
The effect of sugar types, age of culture, and concentrations of 2,4?D and sucrose on somatic embryogenesis was investigated in Cymbopogon schoenanthus subsp. proximus. Six different sugar types: sucrose, fructose, maltose, glucose, galactose and lactose at 3% concentration were used for each of three 2,4?D concentration treatments (1.0, 2.0, 4.0 mg/l). ANOVA showed a significant difference at the 1% level for culture age, sugar types and interactions between 2,4?D and sugar types when mean embryo numbers of individual sugars across the four culture ages are compared. Maltose gave highest mean value, followed by sucrose and the lowest mean number was recorded with galactose. Cultures induced by galactose although low in embryo induction gave the highest mean number of shoots across the different media and culture age. Effect of different concentrations of sucrose and BA on production of number of immature somatic embryos, mature germinating somatic embryos and shoots was examined by culturing 2.5 month?old seed?derived callus onto MS medium containing 4 different sucrose concentrations (1.0, 2.0, 3.0, 4.0 %) in combination with different BA concentrations (0.0, 0.025, 0.05, 0.1 mg/l). ANOVA showed significant differences at 1% level for culture age, and interactions between culture age and sucrose concentrations. Mean number of shoots on 1% sucrose for 7 months old culture was 9.4 significantly higher than number produced on all of sucrose concentrations. The efficient regeneration system will be useful for the future production of high yielding genotypes and for the conservation of the species germplasm.Plant Tissue Cult. & Biotech. 25(1): 51-62, 2015 (June)